RAQAMLI TRANSFORMATSIYANING NAZARIY-METODOLOGIK ASOSLARI VA MINTAQAVIY IQTISODIYOTGA TA’SIRI (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The article analyzes the issues of effective management of digital transformation processes in the regional economy. The study scientifically substantiates the ways to ensure economic growth through the use of digital technologies, the digitalization of public administration, the development of a data ecosystem, and the improvement of decision-making systems based on artificial intelligence and Big Data technologies. Using the case of the Bukhara region, indicators of the digital economy are analyzed, and practical recommendations are proposed for developing a digital model of regional development.